ASSESMENT THE EFFECTIVENESS OF MINIMALLY INVASIVE SURGICAL METHODS IN ACUTE CHOLECYSTITIS - Ergashev Ulugbek Yusufjanovich; Zokhirov Adkhamjon Rafiqovich; Mominov Alisher Tashkarganovich; Gafurov Behzod Tohirovich (Scientific Trends, 2023)
The treatment of obstructive jaundice is a complex problem in modern surgery. Progressive hepatic failure is the main cause of unsatisfactory treatment results in patients with this syndrome, leading to death in the postoperative period in 53-64% of cases. Significant violations of the functional state of the liver, the development of dystrophic and destructive transformation of hepatocytes, causing liver failure, develop in connection with insufficiently effective preoperative treatment.
Keywords: obstructive jaundice, transhepaticendobiliary, biliary hypertension, “Beckon” analyzer